INTERSCALAR VEHICLES FOR AN AFRICAN ANTHROPOCENE: On Waste, Temporality, and Violence - HECHT, GABRIELLE (Cultural anthropology, 2018)
How can we incorporate humanist critiques of the Anthropocene while harnessing the notion’s potential for challenging political imagination? Placing the Anthropocene offers one way forward; the notion of an African Anthropocene offers a productive paradox that holds planetary temporality and specific human lives in a single frame. Navigating the Anthropocene from Africa requires attending to scale both as an analytic and an actor category. In order to do so, this essay proposes the notion of interscalar vehicles: objects and modes of analysis that permit scholars and their subjects to move simultaneously through deep time and human time, through geological space and political space. This essay discusses the creation and destruction of value/waste and pasts/futures around a uranium mine in Mounana, Gabon, to unpack the political, ethical, epistemological, and affective dimensions of interscalar vehicles and their violent Anthropocenic implications.